The labor market situation of women in the Visegrad countries - Ewa Cukrowska-Torzewska; Anna Lovasz; Mariann Rigo (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
The Visegrad 4 countries are characterized by low female and maternal employment rates compared to other Western and Nordic countries. Employment rates of mothers with children aged 0-2 years old are especially low, except in Poland. Work-family balance indicators and gender wage gaps are also unfavorable. The poor labor market situation of mothers in V4 countries has to do with the peculiarities of the national family policies: excessively long parental leaves coupled with poor childcare coverage for children under the age of 2. The only exception is Poland, which provides a shorter leave of 1 year. Though parental leaves are aimed at both parents, the provision of leaves for the exclusive use of fathers is low. Company-level corporate attitudes also play a role. Specifically, part-time work and time flexibility of working hours could be useful tools, however, they are scarcely used in V4 countries compared to other countries in Europe.
Keywords: J08; J16; J21; 330; Female employment; maternal employment; gender gaps; family policies; company level institutions